Dual Sub‐Cells Modification Enables High‐Efficiency n–i–p Type Monolithic Perovskite/Organic Tandem Solar Cells. (17th January 2023) - Yao, Qin; Xie, Yue‐Min; Zhou, Yingzhi; Xue, Qifan; Xu, Xin; Gao, Yujia; Niu, Tianqi; Chu, Linghao; Zhou, Zhisheng; Lin, Francis R.; Jen, Alex K.‐Y.; Shi, Tingting; et al.
Abstract: Monolithic perovskite/organic tandem solar cells (POTSCs) have attracted increasing attention owing to ability to overcome the Shockley–Queisser limit. However, compromised sub‐cells performance limits the tandem device performance, and the power conversion efficiency (PCE) of POTSCs is still lower than their single‐junction counterparts. Therefore, optimized sub‐cells with minimal energy loss are desired for producing high‐efficiency POTSCs. In this study, an ionic liquid, methylammonium acetate (MAAc), is used to modify wide‐bandgap perovskite sub‐cells (WPSCs), and bathocuproine (BCP) is used to modify small‐bandgap organic solar cells. The Ac − group of MAAc can effectively heal the Pb defects in the all‐inorganic perovskite film, which enables a high PCE of 17.16% and an open‐circuit voltage ( V oc ) of 1.31 V for CsPbI2.2 Br0.8 ‐based WPSCs. Meanwhile, the BCP film, inserted at the ZnO/organic bulk‐heterojunction (BHJ) interface, acts as a space layer to prevent direct contact between ZnO and the BHJ while passivating the surface defects of ZnO, thereby mitigating ZnO defect‐induced efficiency loss. As a result, PM6:CH1007‐based SOSCs exhibit a PCE of 15.46%. Integrating these modified sub‐cells enable the fabrication of monolithic n–i–p structured POTSCs with a maximum PCE of 22.43% (21.42% certified), which is one of the highest efficiencies in such type of POTSCs. Abstract : Ionic liquid methylammonium acetate and bathocuproine are used to modify wide‐bandgap perovskite sub‐cells and small‐bandgap organic solar cells, respectively, enabling n–i–p structure perovskite/organic tandem solar cells with a maximum power conversion efficiency of 22.43% (21.42% certified).